PERLINDUNGAN HUKUM TERHADAP KONSUMEN KARTU SIM YANG MENGALAMI KEBOCORAN DATA AKIBAT PERETASAN - Fadhi Khoiru Nasrudin; Rosalinda Elsina Latumahina (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
The development of the internet cannot be separated from the development of the concept of personal data. Information technology today has developed very quickly and rapidly. This is because information technology is able to eliminate the boundaries of space, distance and time so as to significantly increase aspects of productivity and efficiency. The presence of digital crime has developed into a threat to human life, making it difficult for public authorities to know the strategies for violations committed with computer innovation, especially internet networks. So the main problem in this research is whether the Personal Data Protection Law can protect SIM card consumers against hacking of personal data? Data protection is a term that is often used to refer to binding practices, safeguards and rules put in place to protect personal data and ensure that the data subject remains in control. Article 12 paragraph (1) Personal Data Subjects have the right to sue and receive compensation for violations of processing Personal Data about themselves in accordance with statutory provisions. The approach to this problem is to use a method that reviews the regulations and provisions that have been in force and are often followed by the community. Therefore, the type of research used includes normative legal research